Abstract on the conferece "A ‘Reasonable Choice’ Approach to Turnout" - Grofman, Bernard (My University, 2018)
The Central puzzle we seek to address is “Why does what is arguably the most plausible account of the decision to vote or not to vote, namely the rational choice model proposed by Anthony Downs (1957), apparently go so badly awry in predicting voter’s turnout decisions?”. We offer an alternative “reasonable choice” approach (Grofman, 1999) with three key features. First, we replace the usual Downsian model with a two-parameter approach to the calculus of turnout: one a motivational factor, M, that is independent of election contest specific factors or expected current election contest outcomes, and the second, E, involving factors tied to the current election, such as the nature of the campaigning, election day weather, and anticipated current election outcomes. We operationalize this two parameter approach in terms of a threshold-based model of voter participation choices based on ideas in Brians and Grofman (1999) and Arcenau and Nickerson (2009). Second, while the two parameter approach will incorporate the same factors used in rational choice models of turnout -- P, B, C, and D, and emphasizes the usefulness of utility/incentive based approaches to understanding the turnout decision, our approach uses the same factors in a rather different way, in terms a comparative statics approach, i.e., how changes in each of these factors can be expected to affect changes in turnout levels and changes in who votes, rather than examining turnout decisions in a one-shot and individual-choice focused fashion using cross-sectional data. Third, we acknowledge the explanatory limitations of models that are built on a narrow concept of motivation based solely on instrumental considerations at the individual level tied to expected changes in outcome.
Keywords: Elecciones; Tournout; Voting